ortho‐C─H Alkylation of Aryl Chlorides by a Catellani Strategy - Wang, Jian‐Shu; Liu, Zequan; Qian, Guangyin; Chen, Xiahe; Cao, Liming; Yu, Tiaozhen; Ye, Jinxiang; Ma, Yuanyuan; Chen, Shuqing; Yang, Zuo; Cheng, Hong‐Gang; Yang, Yun‐Fang; et al. (Angewandte Chemie International Edition, 2025)
Herein we report a general and practical palladium/norbornene catalysis system that effectively promotes difunctionalization of less reactive aryl chlorides. The key to success lies in the use of a particular norbornene (NBE) derivative as a powerful mediator that synergistically cooperates with the palladium catalyst and an electron‐rich phosphine ligand. A broad spectrum of electronically diverse aryl chlorides (57 examples) delivered the corresponding ortho‐C─H alkylation/ipso‐olefination products in moderate to good yields. Notably, this protocol features excellent functional‐group tolerance, high concentration, scalability, and late‐stage functionalization of complex aryl chlorides. Furthermore, by integrating this chemistry with its counterparts involving aryl iodides and bromides, an intriguing triple‐Catellani reaction sequence was developed, rapidly increasing molecular complexity and diversity. Finally, DFT calculations were performed, revealing that noncovalent C─H⋯O interactions between the XPhos ligand and the NBE mediator promote the pivotal NBE insertion step. Difunctionalization of less reactive aryl chlorides by cooperation of a norbornene (NBE) mediator with a palladium catalyst bearing an electron‐rich phosphine ligand delivered ortho‐C─H alkylation/ipso‐olefination products. The protocol also enabled sequential Catellani reactions to increase molecular complexity. DFT calculations revealed that C─H⋯O interactions between the XPhos ligand and the NBE mediator promote the pivotal NBE insertion step.